Creeks & Southerners : biculturalism on the early American frontier - Frank, Andrew, 1970- (Indians of the Southeast., 2005)
Creeks and Southerners examines the families created by the hundreds of intermarriages between Creek Indian women and European American men in the southeastern United States during the eighteenth and early nineteenth century. Called "Indian countrymen" at the time, these intermarried white men moved into their wives' villages in what is now Florida, Georgia, and Alabama. By doing so, they obtained new homes, familial obligations, occupations, and identities. At the same time, however, they maintained many of their ties to white American society and as a result entered the historical record in large numbers.